2002
DOI: 10.7547/87507315-92-2-90
|View full text |Cite
|
Sign up to set email alerts
|

Limb Salvage in Recurrent Synovial Sarcoma of the Right Ankle and Lower Leg

Abstract: Synovial sarcoma of the extremities represents 7% of all soft-tissue sarcomas. This article presents the case of a patient who was treated for a synovial sarcoma of the lateral aspect of the distal lower leg extending to the ankle and involving the fibular bone. The patient underwent a wide excision of the tumor, including the fibular bone, followed by radiation and chemotherapy, rather than undergo an amputation of the right leg. Consideration is also given to the traumatic etiology of the tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Neoadjuvant and adjuvant therapies represent a critical component of the local control and systemic treatment of patients with STS. 9,17,30,31 Particularly for high grade lesions, limb salvage without chemotherapy or radiation may result in a high rate of local recurrence and relapse. 31,32 Modern radiation therapy can assist in the control of residual microscopic STS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neoadjuvant and adjuvant therapies represent a critical component of the local control and systemic treatment of patients with STS. 9,17,30,31 Particularly for high grade lesions, limb salvage without chemotherapy or radiation may result in a high rate of local recurrence and relapse. 31,32 Modern radiation therapy can assist in the control of residual microscopic STS.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving local tumor control while avoiding amputation and preserving satisfactory function therefore remain the principal challenges in the surgical management of patients with foot and ankle sarcomas. 31…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7,9,15,20,[23][24][25][26] Synovial sarcoma has poor prognosis due to the patterns of recurrence such as local invasion potential along the fascia, regional lymph node metastases and the distant metastases. 22 In this study, even though there is a distinct difference of local control, disease-free and overall survival rates between patients with synovial histopathology and the patients with other histopathology, this difference was not statistically significant. Our patients with local recurrences were controlled with salvage treatments.…”
Section: Discussionmentioning
confidence: 69%
“…13,14,21 Good local control with sparing of limb function using the combined therapeutic approach in the sarcoma of foot has been demonstrated. 3,8,10,22 In the literature, local recurrence rate was 10-14% for STS of the foot. 7,11,13 Temple et al and Kozawa et al reported worse outcomes in patients undergoing amputations compared to patients having limb sparing surgery.…”
Section: Discussionmentioning
confidence: 99%